A bilayer GO/nanofibrous biocomposite coating to enhance 316L stainless steel corrosion performance. (19th June 2019) - Khosravi, Fatemeh; Nouri Khorasani, Saied; Rezvani Ghomi, Erfan; Kichi, Mohsen Karimi; Zilouei, Hamid; Farhadian, Mousa; Esmaeely Neisiany, Rasoul
Abstract: A bilayer coating has been synthesized to be coated on the 316L stainless steel (SS) for bone implant application. The first layer consisted of graphene oxide (GO) which was coated via the electrophoretic deposition method. The second layer including Poly ( ε -caprolactone) (PCL)/Gelatin-forsterite nanofibers was electrospun on the first layer. The morphology of the bare 316L SS, GO-coated, electrospun nanofibers, and nanofibers-coated samples were investigated using scanning electron microscopy (SEM). The electrospun nanofibers were also characterized by Fourier transform infrared spectroscopy (FTIR) and confirmed the presence of PCL, gelatin, and forsterite in the nanocomposite coating. Furthermore, the morphological investigation of the nanofibers revealed that 80:20 weight of PCL to gelatin did not show any beads, making them for coating on the GO coatings. In addition, the corrosion behavior of the coated samples was assessed by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The samples coated with GO and GO/PCL-gelatin-forsterite 1% showed the best corrosion resistance in comparison with other samples. Consequently, the prepared bilayer biocomposite coating including 1 wt% forsterite nanoparticles can be a promising candidate for orthopedic implants.